The ‘Take 5 Voices’ of community music – understanding the lived experiences of a UK community choir through phenomenology - Horner, Kristen (2019)
There currently exists significant methodological issues within CM research, criticised for lack of theoretical grounding and advocacy considerations resulting in uncritical research agendas (Galloway, 2009; Belfiore & Bennett, 2010). These concerns have historically permeated the CM field, and are perceived to have worsened in CM’s acceptance of public sector funding from the 1970s onwards (Kelly, 1984). A research culture of ‘resource’ orientation over ‘active reflexivity’ prevails, in which the evaluation of outcomes are emphasised over the understanding of processes of CM engagement (McKay & Higham, 2012). This dissertation explicitly focuses on these processes of engagement. The adoption of an Interpretative Phenomenological Analysis (IPA) framework set out by Smith, Jarman & Osborn (1999) aimed to understand CM experiences in the ‘wider social, cultural and theoretical context’ of participants’ lives (Larkin, Watts & Clifton, 2006). Through this, the accounts of Take 5 Voices, an inter-generational community choir based in Bulwell, north Nottingham, are heard. Identified themes include degrees of formality within CM, the ‘team’ in Team Take and barriers to CM engagement. Exploring the ‘essence’ of participant experience through IPA resulted in findings that highlight pressing matters of discourse within CM. These include the field’s relations with formalised music education and questions concerning the core intents and purposes of CM research. Future research could further explore a symbiotic relationship development between IPA and the CM field, focusing on processes of engagement over the identification of outcomes.